Who Am I in the Classroom? The Influence of Self-Identity Status on Academic Achievement - Biazon , Brayn; Miclat, Camille Jone; Gomera, Enzo Gabriel; Bautista, Jose Nathaniel (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
The concept of self-identity has been a central theme in research for centuries, exploring the fundamental question of what defines an individual over time. This quantitative study aimed to explore the relationship between self-identity status and academic achievement among 155 senior high school students at the Philippine International School-Qatar, utilizing a stratified random sampling technique. The findings indicated that while the majority of students were performing well academically and had explored various aspects of their personal identity, they were still in a transitional phase of identity development. This suggests that even though students may demonstrate strong academic abilities, their sense of self is still evolving and has not yet fully crystallized. Furthermore, when students were grouped according to their grade level or academic strand, no significant relationship was found between self-identity status and academic achievement. This lack of a clear connection suggests that academic performance may be influenced by other factors, such as teaching methods, external support systems, or individual life circumstances, rather than by self-identity alone. However, a significant relationship emerged when students were grouped by gender, suggesting that gender may influence how self-identity and academic achievement intersect. The study recommends that future research further examine the specific impacts of each identity status on students' academic performance.